DAKWAH MULTI PLATFORM: INTEGRASI WEBSITE, YOUTUBE, DAN INSTAGRAM DALAM PENYEBARAN NILAI ISLAM MULTIKULTURAL: Optimalisasi Website, YouTube, dan Instagram sebagai Ekosistem Dakwah Islam Multiplatform - Wardjo, Amin; Purnomo, Agus; Sulistiyani, Anjar; Salafuddin, Ahmad; Kadarusman, Adang; Waluyo, Agus; Febrianti, Adit; Pardi, Ahmad; Syarifuddin S, Arief; Sanjaya, Basan; Rahdianto, Barmawan; Yusuf, Dedi; Maarij M, Fauzy; Ibrahim, Furqon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze multi-platform da'wah strategies through the integration of websites, YouTube, and Instagram as media for disseminating multicultural Islamic values. This research employs a library research method by examining scholarly literature, academic articles, research reports, and relevant digital sources to identify patterns, concepts, and effective strategies for cross-platform digital da'wah. The findings indicate that multi-platform integration enhances the reach of da'wah, increases message effectiveness, and builds two-way interactions that support the internalization of multicultural Islamic values such as tolerance, respect for diversity, dialogue, and religious moderation. Digital da'wah is no longer limited to information delivery but has transformed into a participatory, adaptive, and responsive communication ecosystem aligned with the dynamics of digital society. This study asserts that the synergy between Islamic content and multicultural principles, when optimized through cross-platform communication design, can serve as an essential pillar for inclusive da'wah in the digital era.